Mercy Otis Warren, the American Revolution and the Classical Imagination - Eran Shalev (Transatlantica)
Students of American history are aware of Greece and Rome’s immense influence on the ideology and political thought of the Founding Era, while scholars of women studies acknowledge Mercy Otis Warren’s importance as a “Founding Mother” of the American republic. This essay focuses on Warren’s remarkable use of the classics in her popular, if now forgotten revolutionary dramas, and in her magisterial history of the Revolution written years later. In her works Warren put to use a set of powerful and unique rhetorical modes for incorporating and merging America and the classical world. The frame of mind that allowed her to present acquaintances as Brutuses and Cassiuses, and American history as a reenactment of Roman annals, enables us to better understand the modes of thought and action that propelled the American Revolution. Focusing on Warren’s rich classicization of revolutionary America offers, then, new perspectives for explaining the meanings that patriots and the citizens of the young United States ascribed to their revolutionary deeds and their young republic. The historical consciousness that underlies Warren’s literary work suggests that at moments the American Revolution was presented and seen, and should thus be understood, as a Roman revolution.